PELAKSANAAN PASAL 47 AYAT (1) PERATURAN DAERAH NOMOR. 4 TAHUN 2010 JO PASAL 3 AYAT (2) PERDA NOMOR 17 TAHUN 2010 TENTANG RETRIBUSI TEMPAT KHUSUS PARKIR (STUDI DISEPANJANG JALAN SUNGAI RAYA DALAM KECAMATAN SUNGAI RAYA) - NIM. A1012151104, TONI FRANDITO (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac The existence of parking along Jalan Sungai Raya Dalam is related to the implementation of Article 47 paragraph (1) of Regional Regulation Number 4 of 2010 in conjunction with Article 3 paragraph (2) of Regional Regulation number 17 of 2010 concerning Retribution for Special Parking Places. To find out the factors that are obstacles so that the implementation of Article 47 paragraph (1) of Regional Regulation Number 4 of 2010 in conjunction with Article 3 paragraph (2) of Regional Regulation number 17 of 2010 concerning Special Parking Retribution has not been implemented as it should. To find out what efforts are being made by the Kubu Raya Regency Government to regulate parking that does not implement Article 47 paragraph (1) of Regional Regulation Number 4 of 2010 in conjunction with Article 3 paragraph (2) of Regional Regulation number 17 of 2010 concerning Retribution for Special Parking Places.The research method used is Juridical-Empirical with a literature approach (Statue approach) and cases (Case approach) by analyzing applicable regulations adapted to the cases raised, the data used is Primary Data including the results of interviews and observations.The research results indicate that the policy of managing and regulating parking, particularly in Sungai Raya District, Kubu Raya Regency, has not been optimal, especially in managing illegal parking. This is due to several obstacles faced by the Parking Management Unit (PMU) in collecting parking fees, such as ineffective planning in setting annual parking targets because it is not supported by accurate data on illegal parking areas exploited for profit along Sungai Raya Dalam road. Consequently, there are still parking areas along Sungai Raya Dalam road without legality, which, if registered with the PMU, would increase parking revenue in Kubu Raya Regency. Organizational issues include the work standards and attitude of parking officers facing personnel shortages, resulting in some officers not adhering to implementation rules, such as working hours. Efforts include providing guidance on parking procedures and socializing policies related to parking regulations. Additionally, the PMU also regulates illegal parking attendants. Supervision by the PMU is still lacking and relies heavily on evaluation reports. For parking managers coordinated by the Kubu Raya Transportation Department, continuous field monitoring will be carried out.Keywords: parking; regional regulations; implementation; Kubu Raya Regency. Abstrak Keberadaan Perparkiran disepanjang jalan Sungai Raya Dalam terkait dengan Pelaksanaan Pasal 47 ayat (1) Peraturan Daerah Nomor 4 tahun 2010 Jo Pasal 3 ayat (2) Perda nomor 17 tahun 2010 tentang Retribusi Tempat Khusus Parkir. Untuk mengetahui factor-faktor yang menjadi kendala sehingga Pelaksanaan Pasal 47 ayat (1) Peraturan Daerah Nomor 4 tahun 2010 Jo Pasal 3 ayat (2) Perda nomor 17 tahun 2010 tentang Retribusi Tempat Khusus Parkir belum dilaksanakan sebagaimana mestinya. Untuk mengetahui upaya apa saja yang dilakukan oleh Pemerintah Kabupaten kubu Raya dalam menertibkan perpakiran yang tidak melaksanakan Pelaksanaan Pasal 47 ayat (1) Peraturan Daerah Nomor 4 tahun 2010 Jo Pasal 3 ayat (2) Perda nomor 17 tahun 2010 tentang Retribusi Tempat Khusus Parkir.Metode penelitian yang digunakan adalah Yuridis-Empiris dengan pendekatan kepustakaan (Statue approach) dan kasus (Case approach) dengan menganalisis peraturan-peraturan yang berlaku disesuaikan dengan kasus yang diangkat, data yang digunakan berupa Data Primer diantaranya, hasil wawancara dan observasi.Hasil penelitian menunjukan bahwa Kebijakan pengelolaan dan penertiban parkir, studi di Kecamatan Sungai Raya Kabupaten Kubu Raya penegelolaan perparkiran khususnya dalam pengelolaan parkir liar belum optimal. Hal ini dikarenakan masih ditemukan beberapa kendala yang menghambat pengelolaan parkir yang dihadapi UPT Parkir dalam hal pemungutan parkir yaitu: rencanaan dalam hal ini penentuan target parkir pertahunnya masih belum efektif karena tidak didukung oleh data-data yang akurat mengenai kawasan-kawasan parkir liar yang dimanfaatkan orang-orang untuk meraub keuntungan di sepanjang jalan Sungai Raya Kecamatan Sungai Raya. Sehingga masih ada kawasan parkir di sepanjang jalan Sungai Raya yang tidak memiliki legalitas yang seyogyanya jika kawasan parkir tersebut terdaftar di UPT Parkir akan menambah penerimaan parkir di Kabupaten Kubu Raya. Pengorganisasian dalam hal ini standar kerja sikap dari petugas parkir yang mengalami kendala dalam jumlah personel, sehingga masih ada beberapa petugas yang belum memenuhi aturan-aturan dalam pelaksanaannya, seperti aturan jam kerja. Penggerakan dalam hal pemberian arahan mengenai tata cara perparkiran dan mensosialisasikan setiap kebijakan yang berkaitan dengan peraturan- peraturan tempat-tempat parkir.Kata Kunci: parkir; peraturan daerah; pelaksanaan; kabupaten kubu raya;